Ectodermal Dysplasia: A Review - Yavuz, Yasemin; Doğan, Mehmet Sinan; Goncharuk-Khomyn, Myroslav (Makara Journal of Health Research, 2021)
Background: Ectodermal dysplasia is a complex group of genetic disorders identified through the abnormal development of ectodermal structures. It is a genetic disorder that affects the development or functions of tissues such as the teeth, hair, nails, and sweat glands. Methods: This review aimed to introduce the outcomes and increase awareness of ectodermal dysplasia reviewing by the literature. Results: The characteristic features of this disease, including hypodontia, hypohidrosis, and hypotrichosis, have been discussed. Conclusions: Ectodermal dysplasia is a heterogeneous group of hereditary disorders with similar clinical findings. It leads to the development of tissue malformations and affects the quality of life of the patient. This review demonstrates that dentists can provide viable and safe alternative conventional treatment modalities for oral rehabilitation in patients with ectodermal dysplasia.